2017
DOI: 10.18632/oncotarget.14570
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of glucose transporter-1 and glucose transporter-3 for survival of cancer patients: A meta-analysis

Abstract: Background and ObjectiveThe role of glucose transporters in cancers remains contradictory. We conducted a systematic review and meta-analysis to assess the association between overall survival and glucose transporter s (GLUTs) 1 and 3 to find an accurate prognostic biomarker.MethodsWe systematically searched the PubMed, EMbase and Medline databases for relevant published studies that were consistent with the eligible criteria up to January 2016, and calculated pooled estimated hazard ratios of GLUT-1 and -3′s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
3
28
1
Order By: Relevance
“…Subgroup analysis indicated high GLUT-1 expression was significantly associated with poor OS in gastric cancer (HR = 1.858, 95%CI: 1.365–2.351; P < 0.0001), urinary carcinoma (HR = 4.589, 95% CI: 1.523–7.655; P = 0.003), ovarian carcinoma (HR = 1.823, 95%CI: 1.163–2.482; P < 0.0001); oral squamous cell carcinomas (HR = 2.224, 95% CI: 1.141–3.306; P < 0.0001); pancreatic adenocarcinoma (HR = 1.729, 95% CI: 1.177–2.282; P < 0.0001); colorectal cancer (HR = 1.473, 95% CI: 0.968–1.979; P < 0.0001); lung cancer (HR = 2.026, 95% CI: 1.278–2.775; P < 0.0002), gallbladder carcinoma (HR = 3.363, 95% CI: 0.218–6.508; P = 0.036), esophageal squamous cell carcinoma (HR = 1.815, 95%CI: 0.779–2.85; P = 0.001). These results were partly consistent with the previous study reported by Xiu Chen et al, which found the correlation of GLUT-1 up-regulation and negative OS in pancreatic and gastric cancer but not in colorectal cancer [ 67 ]. Unfortunately, we could not gather information from the other 12 cancer types because only a single study was involved in each subgroup.…”
Section: Resultssupporting
confidence: 93%
“…Subgroup analysis indicated high GLUT-1 expression was significantly associated with poor OS in gastric cancer (HR = 1.858, 95%CI: 1.365–2.351; P < 0.0001), urinary carcinoma (HR = 4.589, 95% CI: 1.523–7.655; P = 0.003), ovarian carcinoma (HR = 1.823, 95%CI: 1.163–2.482; P < 0.0001); oral squamous cell carcinomas (HR = 2.224, 95% CI: 1.141–3.306; P < 0.0001); pancreatic adenocarcinoma (HR = 1.729, 95% CI: 1.177–2.282; P < 0.0001); colorectal cancer (HR = 1.473, 95% CI: 0.968–1.979; P < 0.0001); lung cancer (HR = 2.026, 95% CI: 1.278–2.775; P < 0.0002), gallbladder carcinoma (HR = 3.363, 95% CI: 0.218–6.508; P = 0.036), esophageal squamous cell carcinoma (HR = 1.815, 95%CI: 0.779–2.85; P = 0.001). These results were partly consistent with the previous study reported by Xiu Chen et al, which found the correlation of GLUT-1 up-regulation and negative OS in pancreatic and gastric cancer but not in colorectal cancer [ 67 ]. Unfortunately, we could not gather information from the other 12 cancer types because only a single study was involved in each subgroup.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, there is also evidence that elevated glycolysis confers a proliferative advantage upon cancer cells over and above maintaining ATP production (Hay, 2016). Both hypoxia and high levels of glucose uptake are associated with poor prognosis (Chen et al, 2017; Kunkel et al, 2003). However, high rates of glycolysis are also a feature of normal cells with high rates of proliferation which may lead to on-target toxicities with prolonged high-dose treatment with glycolysis inhibitors such as 2DG.…”
Section: Discussionmentioning
confidence: 99%
“…In IDH1 +/+ and IDH1 R132H/+ cells, GLUT1 and GLUT3 levels were reduced upon treatment with VC. As overexpression of these transporters is associated with poor survival in several cancers [44], we purpose a positive outcome of high-dose VC treatment as therapeutical avenue in IDH1 +/+ and IDH1 R132H/+ cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mutated cells showed an increased GADD45a mRNA expression. Frequently, cancer cells show a high expression of glucose transporters GLUT1 and GLUT3 due to the metabolic changes and high demands of energy through neoplastic transformation [43][44][45]. In IDH1 +/+ cells, GLUT1 and GLUT3 were significantly reduced upon treatment with VC, whereas in IDH1 R132H/+ cells also a reduction, though to a smaller extent, was detected.…”
Section: -Hg Levels In Idh1 R132h/+ Cells Decrease Upon Treatment Wimentioning
confidence: 99%